Generation of Orbital Angular Momentum Beam With Circular Polarization Ceramic Antenna Array - Ke Bi; Jianchun Xu; Daquan Yang; Yanan Hao; Xinlu Gao; Shanguo Huang (IEEE Photonics Journal)
Orbital angular momentum (OAM) beams can be generated at many microwave frequencies by using antenna array. However, the complexity of the system and inability to transmit over long distances limit the applications of OAM beams in the radio domain. Here, a significantly simplified global positioning system (GPS) ceramic antenna array is employed to generate OAM beams without the assistance of phase shifting devices. Simulation of the GPS ceramic antenna array verifies that the OAM beams with the mode of ±1 show small divergence angle and very standard spiral phase distribution. To test the transmission capability of the proposed antenna array, a measurement system that can detect the one-dimension spatial distribution of electromagnetic characteristic for the OAM beams is set up. Even considering the enormous loss in cables and power divider, the receiving antenna still can receive the electromagnetic characteristic of the OAM beams at a place more than 2 m away from the antenna array. Experimental results presented in this paper demonstrate the excellent performance of the OAM beams when generated with the proposed ceramic antenna array configuration.